Systematic Literature Review on Speaking Assessment Practices in EFL Contexts - Farah Nurkumaila; Zian Salma; Azifah Hafizha Husnullah; Ratna Sari Dewi; Reza Anis Maulidya (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
Speaking assessment is essential for evaluating EFL learners’ communicative competence, yet it remains challenging due to issues of validity, reliability, and authenticity. This study conducts a Systematic Literature Review (SLR) of empirical research on speaking assessment practices in EFL contexts from 2015 to 2025, using the SALSA framework for methodological rigor. Fourteen studies were analysed thematically. The findings show that performance-based and technology-integrated assessments are the most dominant approaches, while rater bias, limited assessment literacy, and learner anxiety remain key challenges. The review highlights the importance of balancing fairness, practicality, and authenticity in evaluating speaking performance. It also emphasizes the potential of formative and technology-supported assessments to enhance feedback and learner engagement. The results also provide valuable insights for EFL teachers and policymakers in developing more effective and equitable speaking assessment practices. Pedagogically, the review underscores the need to strengthen teachers’ assessment literacy so that they can design and apply rubrics, provide formative feedback, and interpret speaking scores accurately. Theoretically, this study contributes to the understanding of how various assessment practices interact within the broader EFL teaching-learning process. Future studies are encouraged to explore longitudinal evidence of how integrated assessment frameworks influence EFL learners sustained speaking improvement, motivation, and classroom participation.